Pengaruh Disiplin Kerja dan Job Description Terhadap Kinerja Karyawan Pada PT. Oasis Water Internasional Banyuasin Sumatera Selatan - Shaputra, Muhammad Hendra; Afriyani, Fauziah; Purnamasari, Endah Dewi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Work discipline is an important factor that reflects the level of employee compliance with the regulations and standards set by the company. Meanwhile, a clear and detailed job description helps employees understand their duties and responsibilities, thereby increasing work efficiency and effectiveness. The research method used is quantitative with data collection through questionnaires distributed to employees at PT. Oasis Water Internasional Banyuasin South Sumatra. Data analysis was carried out using linear regression techniques to determine the extent to which work discipline and job descriptions affect employee performance. The results of the study showed that both work discipline and job descriptions have a positive and significant influence on employee performance. Thus, companies need to pay attention to and strengthen these two aspects to improve employee productivity and work quality.